Kompozycja literacka Sdz 1 - Szwarc, Urszula (The Biblical Annals, 2017)
The article considers Jg. 1 as a separate pericope. Its detailed analysis from the point of view of literary structure and sources used in the composition of the text leads to the following conclusions. The content of the text makes it possible to distinguish two main traditions, vv. 2-20.36 and vv. 21-27. 29-35, supplemented with editorial comments of a fairly late date (vv. 1. 28). The traditions differ as to their literary genre. The information contained in Jg. 1 mostly dates back to the times of the judges. The editorial work is marked by respect for old documents, which results in some inconsistencies and breaks in the flow of the narrative. The distinctive nature of much of the information in either tradition suggests that an editor from Judah was responsible for the final form of Jg. 1.